Correlation of Polymerization Conditions with Thermal and Mechanical Properties of Polyethylenes Made with Ziegler-Natta Catalysts - M. Anwar Parvez; Mostafizur Rahaman; M. A. Suleiman; J. B. P. Soares; I. A. Hussein (International Journal of Polymer Science)
In this study, the synthesis of polyethylenes has been carried out with titanium-magnesium supported Ziegler-Natta catalysts in laboratory-scale reactors. A correlation of different polymerization conditions with thermal and mechanical properties of polyethylenes has been established. It is seen that there is lowering of molecular weight (Mw), polymer yield, and catalyst activity at high hydrogen pressure and high temperature. The Mw, polymer yield, and catalyst activity are improved with the increase in ethylene pressure. Dynamic mechanical analysis (DMA) results show that the increase in temperature and hydrogen pressure decreases storage modulus. The samples with higher Mw showed high activation energy. The melting point decreases with the increase in hydrogen pressure but increases slightly with the increase in ethylene pressure. It is seen that the increase in reaction temperature, ethylene pressure, and hydrogen pressure leads to an increase in crystallinity. The tensile modulus increases with the increase in hydrogen pressure and can be correlated with the crystallinity of polymer. The Mw has a major influence on the flow activation energy and tensile strength. But the other mechanical and thermal properties depend on Mw as well as other parameters.